Therapeutic Drug Monitoring of Antibiotic Drugs in Patients Receiving Continuous Renal Replacement Therapy or Intermittent Hemodialysis: A Critical Review. Issue 1 (February 2022) - Matusik, Elodie; Boidin, Clément; Friggeri, Arnaud; Richard, Jean-Christophe; Bitker, Laurent; Roberts, Jason A.; Goutelle, Sylvain
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: Antibiotics are frequently used in patients receiving intermittent or continuous renal replacement therapy (RRT). Continuous renal replacement may alter the pharmacokinetics (PK) and the ability to achieve PK/pharmacodynamic (PD) targets. Therapeutic drug monitoring (TDM) could help evaluate drug exposure and guide antibiotic dosage adjustment. The present review describes recent TDM data on antibiotic exposure and PK/PD target attainment (TA) in patients receiving intermittent or continuous RRT, proposing practical guidelines for performing TDM. Methods: Studies on antibiotic TDM performed in patients receiving intermittent or continuous RRT published between 2000 and 2020 were searched and assessed. The authors focused on studies that reported data on PK/PD TA. TDM recommendations were based on clinically relevant PK/PD relationships and previously published guidelines. Results: In total, 2383 reports were retrieved. After excluding nonrelevant publications, 139 articles were selected. Overall, 107 studies reported PK/PD TA for 24 agents. Data were available for various intermittent and continuous RRT techniques. The study design, TDM practice, and definition of PK/PD targets were inconsistent across studies. Drug exposure and TA rates were highly variable. TDM seems to be necessary to control drug exposure in patients receiving intermittent and continuous RRT techniques, especially for antibiotics with narrow therapeutic margins and in critically ill patients. Practical recommendations can provide insights on relevant PK/PD targets, sampling, and timing of TDM for various antibiotic classes. Conclusions: Highly variable antibiotic exposure and TA have been reported in patients receiving intermittent or continuous RRT. TDM for aminoglycosides, beta-lactams, glycopeptides, linezolid, and colistin is recommended in patients receiving RRT and suggested for daptomycin, fluoroquinolones, and tigecycline in critically ill patients on RRT.